2010
DOI: 10.1002/ibd.21301
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of epithelial gene expression profiles for response to infliximab in Crohnʼs disease‡

Abstract: This study identified a 100% accurate predictive gene signature for (non)response to IFX in CDc, whereas no such a predictive gene set could be identified for CDi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 19 publications
3
112
1
1
Order By: Relevance
“…We were able to characterize robust gene expression differences associated with deep ulcers and enriched pathway associations with oxidative stress and Th1 polarization. These data can serve to direct future therapy for ileal mucosal healing, which may not be achieved with current approaches (12). In contrast, we were able to detect an association between depletion of specific Firmicutes and Bacteroidetes taxa and expansion of Proteobacteria and clinical severity, as measured by the PCDAI.…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…We were able to characterize robust gene expression differences associated with deep ulcers and enriched pathway associations with oxidative stress and Th1 polarization. These data can serve to direct future therapy for ileal mucosal healing, which may not be achieved with current approaches (12). In contrast, we were able to detect an association between depletion of specific Firmicutes and Bacteroidetes taxa and expansion of Proteobacteria and clinical severity, as measured by the PCDAI.…”
Section: Methodsmentioning
confidence: 56%
“…The use of gene expression or microbial markers to support diagnosis and adjust therapy for specific subsets of IBD is currently limited. In one single-center study, researchers tested for association between ileal or colonic gene expression and subsequent clinical and mucosal response to anti-TNF-α therapy in adults with established CD (12). Overall, 12 of 19 patients experienced healing of colonic ulcers with anti-TNF-α, and baseline expression of specific colonic genes was associated with subsequent response.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the tissue sampling and microchip array analysis methods used in the present study yielded results that indicated patterns of gene expression in dogs with CE were broadly similar to those in humans with IBD, including expression of genes regulating immune and inflammatory responses, metabolism, cell proliferation, and epithelial structure and function. 8,[54][55][56][57][58][59][60][61][62] Results of the present study indicated that the expression of multiple genes regulating mucosal inflammation was markedly altered in dogs with CE, compared with that in healthy control dogs. The differential expression of several genes (fatty acid-binding protein 6, metallothionein 1E, claudin 8, matrix metallopeptidase 1, peroxisome proliferator-activated receptor γ, S100 calcium-binding protein G, and solute carrier family 40 member 1) between groups of dogs in the present study indicated that the molecular pathogenesis of CE in dogs may be similar to that in chronic immune-mediated intestinal inflammation in humans with IBD.…”
Section: Discussionmentioning
confidence: 54%
“…Ready access to disease tissue in UC in the form of biopsies from colonoscopy has prompted a number of transcriptomic studies. One study from the Leuven group identifi ed a composite gene expression signature in mucosal biopsies associated with high sensitivity and specifi city for response to infl iximab ( 81 ). Using a similar strategy another study identifi ed a gene signature associated with non-response to medical therapy in UC.…”
Section: Anti-tnf and Anti-integrin Therapymentioning
confidence: 99%